2022
DOI: 10.7759/cureus.25673
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Culture and Scanning Electron Microscopic Evaluation of Endodontic Hand Files: An In Vitro Study

Abstract: Background Endodontic hand files are used during root canal treatment in the cleaning and shaping step of the procedure. Whether endodontic instruments should be single-use or reusable is a topic of debate. This in vitro study aimed to analyze the bioburden on used and new sterilized endodontic hand files. Methodology A total of 30 K-files (15 used, 15 new) and 30 H-files (15 used, 15 new) were studied. After clinical use, the used and new files were subjected to phloxine B sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…No matter what kind of cleaning method was used before, NiTi files were treated with steam sterilization. In addition to this, the results of a recently published study showed negative tests for bacterial culture (100%) among new H&K-types hand endodontic files after sterilization [24]. Although bacterial growth on files taken from the manufacturer's packing is considered to be limited, Standards Australia [25] recommends that files be sterilized in suitable packaging before use to assure instrument's sterility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No matter what kind of cleaning method was used before, NiTi files were treated with steam sterilization. In addition to this, the results of a recently published study showed negative tests for bacterial culture (100%) among new H&K-types hand endodontic files after sterilization [24]. Although bacterial growth on files taken from the manufacturer's packing is considered to be limited, Standards Australia [25] recommends that files be sterilized in suitable packaging before use to assure instrument's sterility.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, only aerobic bacteria were detected in this study due to the environment of these bacteria [ 32 ]. No anaerobic bacteria were observed in this experiment due to all the investigated samples were new packed endodontic files without sterilization before clinical use compared to sterilized/non-sterilized after clinical use which illustrated high evidence of anaerobic bacteria among the investigated endodontic files [ 23 , 24 ]. Thirdly, only one size of K-file was investigated in this experiment; however, the size and design of the cross-section could contribute to the amount of debris retained during manufacturing between the flutes.…”
Section: Discussionmentioning
confidence: 99%
“…A direct inoculation sterility testing was performed on the sterilized dried SAP powders and baking sheet in an aseptic room to critically assess whether the sterilized materials were free from contaminating viable microorganisms and to confirm the reusability of the materials towards the DW-TENG fabrication. Initially, a sterile nutrient broth culture media was prepared, and the test samples from both materials were incubated at 37 ºC and monitored continuously for 14 days [41] . Positive and negative controls were used to compare the test results of the materials.…”
Section: Selection Of Materialsmentioning
confidence: 99%